PENGARUH PENYAKIT KARDIOVASKULAR TERHADAP MORTALITAS PASIEN COVID-19 TAHUN 2019-2020 : SYSTEMATIC REVIEW - Sarah Adhiningtias; Soroy Lardo; Yudhi Nugraha (2021)
In December 2019, Wuhan, China, became the center of an outbreak of pneumonia cases caused by the Coronavirus. The virus is included in Beta coronavirus and named as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) or Coronavirus Disease 2019 (COVID-19) which until now has become a pandemic. Comorbid such as Hypertension, Coronary Artery Disease, and DM are suspected to be risk factors for the severity and mortality. Until now, data regarding this matter is still incomplete and being researched. This study aims to determine the effect of Coronary Artery Disease and Diabetes Mellitus on mortality of COVID-19 patients in 2019-2020 using a systematic review method. Journal searches conducted from June to December 2020 with the keywords (COVID-19 OR SARS-CoV-2) AND (Cardiovascular Disease) AND (Hypertension OR Coronary Artery Disease) AND (Diabetes Mellitus) AND (Mortality) and selected by PRISMA-P method. Journals are assessed using the Quality Assessment Criteria compiled by JBI (Joanna Briggs Institute). There were 7 journals synthesized based on inclusion and exclusion criteria. This study proves that hypertension, DM, and CAD have an effect on mortality, most of the patients died due to multi-organ failure. Lab examination results such as troponin, d-dimer, and procalcitonin levels can support the patient's possible prognosis.